Experimental study on laser peen forming of aluminium alloy 2024-T351 plate. Issue 1 (1st December 2022) - Huang, X; Zeng, Y S; Wang, M T; Zou, S K
Abstract : Laser peen forming technology LPF is proposed on the basis of laser peen strengthening technology and mechanical peen forming technology. It is an advanced high-efficiency and long-life manufacturing technology for panels. This forming technology has a wide application prospect in the field of aerospace manufacturing. In the forming process, there are many factors affecting the forming process, such as laser pulse energy, shot peening times, shot peening path, material, structure and so on. At present, there are few studies on the influence of laser peen forming process parameters on the shape of parts, which can not meet the technical requirements of forming process. In this paper, based on the single curvature bending forming of al2024-T351 aluminum alloy, the elastic-plastic deformation of metal surface formed by laser shot peening is investigated. The spot morphology formed by laser shot peening is analyzed. The influence law of different forming process parameters on the forming shape of parts is established. The results show that the thickness is the main influencing factor for the curvature radius of the impact area. The radius of curvature increases with the increase of thickness, and decreases with the increase of pulse energy and coverage. Using the regression analysis method, the mathematical model of laser peen forming curvature radius is established. The predicted results are consistent with the experimental results, and the maximum relative deviation is 2.6%.